Nanoemulsions in CNS drug delivery: recent developments, impacts and challenges. Issue 5 (May 2019) - Karami, Zahra; Saghatchi Zanjani, Mohammad Reza; Hamidi, Mehrdad
Highlights: Nanoemulsions are among promising nanocarriers for various biomedical applications. Biocompatibility and simplicity are the most important advantages of nanoemulsions. Nanoemulsions have shown brilliant results in studies treating neurological diseases. Nanoemulsion-based therapeutic cargo can be considered as future CNS disease therapy. Abstract : Despite enormous efforts, treatment of CNS diseases remains challenging. One of the main issues causing this situation is limited CNS access for the majority of drugs used as part of the therapeutic regimens against life-threatening CNS diseases. Regarding the inarguable position of the nanocarrier systems in neuropharmacokinetic enhancement of the CNS drugs, this review discusses the latest findings on nanoemulsions (NEs) as one of the most promising candidates of this type, to overcome the challenges of CNS drug delivery. Future development of NE-based CNS drug delivery needs to consider so many aspects not only from a physicochemical point of view but also related to the biointerface of these very small droplets before achieving clinical value. Teaser: Nanoemulsions are among the most promising future drug carriers with remarkable potential for the brain delivery of a wide variety of drugs.